EVOLUTIONARY PLACTICITY OF HIGHLY SPECIALIZED ORGANISMS: EVOLUTION OF ERIOPHYOID MITES (ACARIFORMES: ERIOPHYOIDEA) ON PLANTS (Acta Entomologica Serbica, 2015)
Eriophyoids are highly specialized plant-feeding acarifom mites. As a result of miniaturization and adaptation to phytoparasitism they lacked III and IV pairs of legs and acquired elongated vermiform body, unique structure of gnathosoma and peculiar anatomy. Despite the high degree of specialization eriophyoid mites demonstrate remarkable evolutionary plasticity which manifests itself in numerous morphoilogical reversia, parallelisms and modifications associated with occupying of a variety of niches, processes of gall formation, transitions to new groups of hosts and various adaptations to climate change.